(untitled) (Colloquia Comparativa Litterarum, 2025)
In analysing apocalyptic discourse, it is essential to distinguish the spatial and temporal dimensions in which a catastrophe exerts influence, paves the way for the development of a particular way of thinking, and accordingly builds an appropriate and distinct worldview. My goal is to explore some of the consequences of putting discourse into action to affect political or social change. It is important to understand how certain beliefs and conventions are constructed through the use of catastrophic language, symbolism, and imagery. To this end, I will examine how apocalyptic discourse shapes the way people see the world around them, using as examples works by Mario Sironi, Ludwig Meidner, and Stanley Donwood, while comparing them to the Benjaminean notion of “destructive character”, emphasising how the visual discourse structures space and time to unveil novel aspects of reality.